Chitosan nanoparticles triggered the induction of ROS-mediated cytoprotective autophagy in cancer cells. (31st October 2018) - Wang, Hao; Yu, Xiwei; Su, Chang; Shi, Yijie; Zhao, Liang
Abstract: There is a close relationship between autophagy and apoptosis during cancer cell death. We used chitosan nanoparticles (CS NPs) to explore the effects of internalized NPs on the induction of autophagy and to confirm the role of autophagic responses elicited by nanomaterials on the tumour cell's fate. CS NPs at nontoxic concentrations ranging from 10–100 μg/mL triggered the induction of autophagy. With the addition of CS NPs, the aggregation of endogenous LC3 was significantly enhanced and acidic autophagic bodies had been accumulated. CS NPs significantly triggered the occurrence of autophagy by increasing the ratio of LC3 II to LC3 I and CS NPs-mediated autophagy was implicated in reactive oxygen species (ROS) generation and the ROS scavenger N-acetylcysteine (NAC) attenuated CS-induced autophagy. The addition of blank NPs produced a negative effect on cytotoxicity and cellular apoptosis of free Dox, and with the pre-treatment of chloroquine (CQ) as a known autophagy inhibitor, the inhibition rates of cells treated with the combination of Dox and blank CS NPs had been significantly increased. The findings demonstrated that CS NPs have the ability to induce protective autophagy via ROS generation and they were believed to inhibit tumour cell death.